2016
DOI: 10.1128/mcb.00048-16
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of the Yeast Spindle Pole Body Once per Cell Cycle

Abstract: bThe yeast spindle pole body (SPB) is the functional equivalent of the mammalian centrosome. Centrosomes and SPBs duplicate exactly once per cell cycle by mechanisms that use the mother structure as a platform for the assembly of the daughter. The conserved Sfi1 and centrin proteins are essential components of the SPB duplication process. Sfi1 is an elongated molecule that has, in its center, 20 to 23 binding sites for the Ca 2؉ -binding protein centrin. In the yeast Saccharomyces cerevisiae, all Sfi1 N termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 67 publications
(120 reference statements)
1
42
0
1
Order By: Relevance
“…The presence of multiple microtubule organizing centers in apicomplexan parasites (MTOCs; centrosome/centrocone and apical complex)(30, 31) sets these parasites apart from well studied eukaryotic models (yeast and mammalian cells) that have a single MTOC during interphase (32).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of multiple microtubule organizing centers in apicomplexan parasites (MTOCs; centrosome/centrocone and apical complex)(30, 31) sets these parasites apart from well studied eukaryotic models (yeast and mammalian cells) that have a single MTOC during interphase (32).…”
Section: Discussionmentioning
confidence: 99%
“…Further work is required to distinguish these models, in particular, assessment of the foci for presence of other SPB proteins and functionality of the foci as MTOCs is required to confirm them as real SPBs. If SPBs are created de novo we would expect that these strains would lose the requirement for proteins with an essential role in SPB duplication, 452 such as Cdc31 [Rüthnick and Schiebel, 2016]. Many mutants have been identified that fail to duplicate their SPBs, for example the original MPS (Mono-Polar Spindle) genes [Winey et al, 1991] however there are fewer cases of genetic perturbations that lead to SPB overduplication.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of a canonical centrosome, yeasts have a spindle pole body (SPB), a layered structure composed of a centriole-less scaffold that similarly recruits γ-tubulin and nucleates microtubules (Cavanaugh and Jaspersen, 2017). The timing and regulation of SPB biogenesis are similar to the one observed in animal centrosomes (Lim et al, 2009;Kilmartin, 2014;Ruthnick and Schiebel, 2016). It is likely that the animal centrosome and yeast SPB evolved from a common ancestral structure that had centrioles ( Figure 1A), as early-diverged basal fungi such as chytrids (e.g.…”
Section: Introductionmentioning
confidence: 99%